Using The Rasch Model to Measure Prospective Elementary Teachers’ Perception toward Sciencepreneurship, Creative Thinking, Career Adaptability, and Personal Goals - Kartika Chrysti Suryandari; Murwani Dewi Wijayanti; Wahyudi (Postgraduate, University of Mataram, 2024)
The challenge for prospective elementary school teachers in generation Z is teacher professionalism related to learning issues, soft skills, and mastery of technology as demands of the 21st century. Multitasking for prospective teachers often occurs and has an impact on learning. This research analyzes prospective elementary school teachers' perceptions of skills, creative thinking, career adaptability, and personal goals related to learning using Rasch model analysis. The survey method was used in this quantitative research. Research participants were selected using a purposive sample of 70 prospective elementary school teachers. Questionnaires were used in data collection to analyze participant perceptions. The questionnaire was filled out using a 1-4 Likert scale, and the data was then analyzed using the Rasch model. Each instrument element is analyzed in more detail in the Rasch model. The results showed that all participants had an average logit item (+1.03 logit). Person reliability is 0.90, and item reliability is 0.95, meaning each statement item describes the participant's perception. Aspects of sciencepreneurship, creative thinking, career adaptability, and personal goals mutually support the professionalism of an elementary school teacher. The recommendation for further research is to use the Rasch model appropriately to identify participant perceptions.